Peran Griya Abhipraya dalam Meningkatkan Kualitas Bimbingan Klien Pemasyarakatan pada Balai Pemasyarakatan Kelas 1 Surabaya - Bintang Wisnu Prameswara; Ali Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Correctional Client is someone who is in community guidance both children and adults dealing with the law at the pre-adjudication to post-adjudication stage organized by Bapas. Bapas is tasked with organizing guidance to provide provisions for clients so that they can reintegrate properly. The implementation of guidance requires adequate resources, effective guidance programs and facilities that support the implementation of activities. The quality of the guidance provided affects the success of the client to reintegrate well in the community so it is important that the guidance to the client has an effective and efficient value. Problems that often arise at Bapas include the empowerment of Pokmas Lipas and the provision of guidance programs linear to the needs of clients. This is added to the imbalance between the number of Community Supervisors and the number of active clients that must be handled. This problem has the potential to lead to the lack of optimal guidance provided, so there is a need for a new thing that can be a platform for Bapas to carry out its work process better, especially in terms of guidance to Correctional Clients. The issuance of Permenkumham Number M.HH-36.OT.02.02 Year 2022 concerning Guidelines for the Establishment and Implementation of Griya Abhipraya is felt to be the answer to the problems faced. This research aims to describe how Griya Ahipraya's role in improving the quality of guidance for Correctional Clients.